2014
DOI: 10.15698/mic2014.12.179
|View full text |Cite
|
Sign up to set email alerts
|

Loss of wobble uridine modification in tRNA anticodons interferes with TOR pathway signaling

Abstract: Previous work in yeast has suggested that modification of tRNAs, in particular uridine bases in the anticodon wobble position (U34), is linked to TOR (target of rapamycin) signaling. Hence, U34 modification mutants were found to be hypersensitive to TOR inhibition by rapamycin. To study whether this involves inappropriate TOR signaling, we examined interaction between mutations in TOR pathway genes (tip41∆, sap190∆, ppm1∆, rrd1∆) and U34 modification defects (elp3∆, kti12∆, urm1∆, ncs2∆) and found the rapamyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Methoxycarbonylmethyl-2-thiouridine (mcm 5 s 2 U) is a modification present at position 34 and is required for the efficient decoding by tRNA Lys UUU (10). The absence of mcm 5 s 2 U mislocalizes Gln3p due to reductions in TOR activity (65). Together with our results, these observations suggest that TOR activity is probably affected by the aberrant translation caused by deficiencies in either modification.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Methoxycarbonylmethyl-2-thiouridine (mcm 5 s 2 U) is a modification present at position 34 and is required for the efficient decoding by tRNA Lys UUU (10). The absence of mcm 5 s 2 U mislocalizes Gln3p due to reductions in TOR activity (65). Together with our results, these observations suggest that TOR activity is probably affected by the aberrant translation caused by deficiencies in either modification.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, Scheidt et al (65) showed in yeast that absence of another tRNA modification altered TOR activity as well. Methoxycarbonylmethyl-2-thiouridine (mcm 5 s 2 U) is a modification present at position 34 and is required for the efficient decoding by tRNA Lys UUU (10).…”
Section: Discussionmentioning
confidence: 99%
“…In support of a specific requirement for ψ38 in tRNA Gln UUG in the event of wobble base hypomodification, strong synthetic growth defects were observed upon combining the deg1 mutation with mutations in Elongator or Urm1 pathway genes, indicative of functional crosstalk between the modifications at position 34 and 38 in tRNA Gln UUG [8,9,38]. Elongator and Urm1 pathway mutants are further known to exhibit shared phenotypes, including translational inaccuracy and sensitivity to TORC1 inhibiting agents such as caffeine or rapamycin and these are synergistically increased in double mutants lacking both modification activities [9,30,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…its absence leads to tRNA modification defects. 16 To assess whether UMAP distance captured known interactions as well as pairwise correlation, we used a dataset of 1060 protein interactions determined from coimmunoprecipitation followed by mass spectrometry. 2 The UMAP clustering data captured these complexes more sensitively and with more precision than previous pairwise correlation-based metrics (AUC pairwise correlation = 0.73, AUC UMAP = 0.84, Figure 2A).…”
mentioning
confidence: 99%